PROBLEM DAN TANTANGAN PENDIDIKAN AGAMA ISLAM (Perspektif Filosofis) - Susanto, Edi (STAIN Pamekasan, 2010)
Abstract: This paper will describe the problems and challenges of islamic religious education, both abstractive philosophical problems and methodological problems of practice. Abstractive philosophical problems are fundamental issues, long term. They are abstract in the sense requiring general thinking formulations. Thus, they require contextualization commentary on each of the times and places. Meanwhile, the methodological problems of practice are the problems of patterns or models of how the socialization and transformation of islamic religious education for muslims. The problems are instrumental, real, and in direct contact with social reality, economic, psychological and practical aspects.